2010
DOI: 10.1063/1.3481674
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor optical amplifier-based heterodyning detection for resolving optical terahertz beat-tone signals from passively mode-locked semiconductor lasers

Abstract: An all-optical heterodyne approach based on a room-temperature controlled semiconductor optical amplifier ͑SOA͒ for measuring the frequency and linewidth of the terahertz beat-tone signal from a passively mode-locked laser is proposed. Under the injection of two external cavity lasers, the SOA acts as a local oscillator at their detuning frequency and also as an optical frequency mixer whose inputs are the self-modulated spectrum of the device under test and the two laser beams. Frequency and linewidth of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The pulse-to-pulse timing jitter of 2.13 and 2.09 fs are obtained from the direct RF linewidth measurement (∆υ RF1 = 0.654 kHz) and the parabolic curve fit of phase noise vs. mode number through RF linewidth (∆υ RF1 = 0.631 kHz), respectively. In the case of a semiconductor passively mode-locked laser, it is shown that due to material nonlinearities and saturated absorber in the gain area, the phase correlation of the optical longitudinal modes can take place resulting in a strong four wave mixing [39]. This is especially true for an active region consisting of QDot or QDash structures.…”
Section: Rf Beating Note and Timing Jittermentioning
confidence: 99%
“…The pulse-to-pulse timing jitter of 2.13 and 2.09 fs are obtained from the direct RF linewidth measurement (∆υ RF1 = 0.654 kHz) and the parabolic curve fit of phase noise vs. mode number through RF linewidth (∆υ RF1 = 0.631 kHz), respectively. In the case of a semiconductor passively mode-locked laser, it is shown that due to material nonlinearities and saturated absorber in the gain area, the phase correlation of the optical longitudinal modes can take place resulting in a strong four wave mixing [39]. This is especially true for an active region consisting of QDot or QDash structures.…”
Section: Rf Beating Note and Timing Jittermentioning
confidence: 99%
“…As was the case for the timing jitter of pulsed sources, a direct measurement of the intensity is not possible at high repetition rates. A technique to overcome this problem has been recently proposed [28]. The approach is to produce a beating between two single mode tunable lasers and to mix this signal in a semiconductor optical amplifier (SOA) together with the optical beat signal to be measured.…”
Section: Rf Linewidthmentioning
confidence: 99%
“…As compared to fiber lasers, semiconductor mode locked lasers bearing the capability of generating ultra short pulses have unique features of compactness and high repetition rate in Terahertz range [1,[5][6][7]. They are of great interest as they can be easily implemented for several applications ranging from high speed optical commu-nication to all optical signal processing including optical sampling and clock recovery [2,[6][7][8]10]. These lasers can be used to generate millimeter or terahertz waves through mode beating process on high bandwidth photo detector which does not require any com-plex setup.…”
Section: Introductionmentioning
confidence: 99%
“…These devices offer cost effective solution for generation of microwave signals at 60 GHz or beyond by direct detection with high speed photo detector. In fact, these devices have already been used for RF signal generation up to 100 GHz [6]. Pulse generation at 370 GHz and 1.1 THz has been demonstrated using MQW InAlGaAs FP lasers with a one-dimensional photonic bandgap embedded in its structure [3,6,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation